1999
DOI: 10.1034/j.1600-0420.1999.770103.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve head sector analysis recognizes glaucoma most effectively around disc poles

Abstract: ABSTRACT.Purpose: To analyze the topography of normal and glaucomatous discs with the goal of developing improved strategies to discriminate between normal and glaucomatous eyes. Subjects and methods: Raster tomography was performed in both eyes of 225 healthy subjects and in 296 eyes of 214 glaucoma patients. Cup area, average cup radius, rim area and minimal rim width were measured in 24 sectors around the optic nerve head at nine different depths from the reference plane. Receiver Operating Curves (ROC) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…These physiologically narrow temporal rims yield wide significance limits for high ranks (Gundersen & Åsman 1997). On the other hand, glaucomatous disc damage is most often observed around the superior and inferior poles of the optic disc where, in normal optic discs, the neuroretinal rim is usually wide (Pedersen & Anderson 1980;Jonas 1989;Gundersen et al 1999). Jonas and co-workers described a change of optic cup configuration from horizontally oval to circular as the earliest visible sign of glaucomatous disc change (Jonas et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These physiologically narrow temporal rims yield wide significance limits for high ranks (Gundersen & Åsman 1997). On the other hand, glaucomatous disc damage is most often observed around the superior and inferior poles of the optic disc where, in normal optic discs, the neuroretinal rim is usually wide (Pedersen & Anderson 1980;Jonas 1989;Gundersen et al 1999). Jonas and co-workers described a change of optic cup configuration from horizontally oval to circular as the earliest visible sign of glaucomatous disc change (Jonas et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In this region, the neuroretinal rim measurements may vary between normal individuals from very high to almost zero. Glaucomatous damage, on the other hand, usually occurs at the superior or inferior poles (Pedersen & Anderson 1980;Jonas 1989;Gundersen et al 1999) where normal variability is considerably smaller.…”
mentioning
confidence: 99%
“…Several partial maps of the topographic correlations have been published. [11][12][13][14] Iester et al 15 found that the superior and inferior 90°sectors were more informative in predicting visual field loss than the temporal or nasal sectors; Gunderseon et al 16 similarly reported that the polar areas of the ONH were more informative for predicting glaucoma. Emdadi et al 17 found that the neuroretinal rim narrowing in the superior and inferior temporal sectors was associated with glaucoma.…”
mentioning
confidence: 94%
“…The database has been described previously [18,19]. All glaucoma subjects were patients at the Department of Ophthalmology, Malmö University Hospital.…”
Section: Methodsmentioning
confidence: 99%